Beneficios de la Hidrocinesiterapia en Fibromialgia - Navarrete Telenchana, David Alexander (2022)
ABSTRACT The research project was established under a bibliographic character, through documentary collections with priority in clinical trials by various authors, to publicize the benefits of hydrokinesitherapy in fibromyalgia, since this type of non-pharmacological treatment has proven to have benefits for this pathology, the main one being the slowing down of the symptoms; reducing body pain, depression and anxiety; assisting this way to improve quality of life in those who suffer from it. At present, fibromyalgia affects the quality of life, affecting the physical, intellectual, and emotional capacity, producing functional deterioration of the body; In this context, there is a lack of knowledge of the benefits of hydrokinesitherapy, for this reason the purpose of the research was to investigate and synthesize the benefits of the aquatic environment together with its thermal and mechanical properties on the population suffering from this pathology. Through the bibliographic search, thirty-five scientific articles on the research topic were selected, which were assessed by the Physiotherapy Evidence Database (PEDro) methodological assessment scale; thus, achieving a score greater than or equal to seven; These findings were summarized in tables for a better understanding; therefore, this research contributes with quality information already existing. Therefore, the information for the development of the research project was obtained from scientific databases such as PEDro, PubMed, ProQuest, and Scopus. Finally, the research project gives a positive result to the benefits of hydrokinesitherapy in fibromyalgia, since it significantly contributes to the slowing down of symptoms in the aquatic environment, together with the relief and improvement of the person's quality of life.